1968
DOI: 10.1055/s-0038-1651184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fibrinolytic and Proteolytic Enzymes in Subcellular Fractions of Human Granulocytes

Abstract: SummaryThe Cohn and Hirsch method was applied for preparation of human granulocyte subfractions. It was found that specific granules contained about 50-60% of the total activity of acid phosphatase, alkaline and acid protease. The activities of fibrinolytic enzymes (plasminogen, activator of plasminogen and spontaneous fibrinolytic activity) were rather equally distributed in all subfractions.A significant rise of a total fibrinolytic activity was found during fractionation. The results suggest the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…This observation is consistent with the results of other studies (11)(12)(13) in which plasmin activity and the antigenic determinants of plasmin were not demonstrable in leukocytes. In contrast, Prokopowicz not only found evidence for the presence of the plasminogen system in leukocytes but also isolated plasminogen from leukocytes (14,17). Our observations do not resolve these apparent inconsistencies; but in preliminary observations, utilizing sensitive radioimmunochemical approaches (25,29), we have detected very low levels of plasmin-related antigens within several leukocyte preparations (nanogram levels per 10' cells).…”
Section: Nonlytic Release Of Fibrinolytic Proteases From Leukocytescontrasting
confidence: 80%
See 3 more Smart Citations
“…This observation is consistent with the results of other studies (11)(12)(13) in which plasmin activity and the antigenic determinants of plasmin were not demonstrable in leukocytes. In contrast, Prokopowicz not only found evidence for the presence of the plasminogen system in leukocytes but also isolated plasminogen from leukocytes (14,17). Our observations do not resolve these apparent inconsistencies; but in preliminary observations, utilizing sensitive radioimmunochemical approaches (25,29), we have detected very low levels of plasmin-related antigens within several leukocyte preparations (nanogram levels per 10' cells).…”
Section: Nonlytic Release Of Fibrinolytic Proteases From Leukocytescontrasting
confidence: 80%
“…Within the confines of the vascular compartment, leukocytes frequently accumulate in complex thrombi consisting of fibrin and platelets (1)(2)(3)(4)(5); whereas in extravascular sites, the migration of leukocytes to sites of injury where fibrin has accumulated is a central feature of the inflammatory response (5)(6)(7)(8)(9). In both circumstances, the interaction of these cells with fibrin may be active rather than passive, based on the morphologic identification of fibrin within leukocytes (5)(6)(7)(8)(9), the accumulation of leukocytes in thrombi relative to their concentration in blood (4), and the demonstration that fibrinolytic activity of leukocytes is not confined to low pH, at which many cathepsins are active, but also is observed at neutral pH (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies indicated that both fibrinogen and fibrin are susceptible to the action of leukocyte enzymes (3)(4)(5) and that the intrinsic enzymatic system of the leukocytes is distinct from plasmin (6)(7)(8)(9)(10). Apparently, intracellular plasminogen does not account for fibrinolysis, as only very low plasminogen levels have been detected in polymorphonuclear leukocytes (8,11,12).…”
Section: Introductionmentioning
confidence: 99%